2018
DOI: 10.5430/jnep.v8n8p86
|View full text |Cite
|
Sign up to set email alerts
|

Association between sleep pattern and body mass index among undergraduate health colleges’ students at Qassim University, Saudi Arabia

Abstract: Background and objective: Better quality and adequate amount of sleep are essential to have better cognitive performance and by contrast, poor bedrest is related to a diminishing of cognitive and psychological functioning and deteriorating physical health. Recently the quality of sleep among various segments of the population has become a focus of continuous research and investigations, where insufficient sleep may lead to adverse cardio-metabolic effects by influencing body weight, blood pressure, and glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…A previous study indicated that longer sleep duration (>9 h) was significantly associated with an increased risk of obesity in adults, while shorter sleep duration had no effect on obesity [ 46 ]. In contrast, other studies showed no evidence that sleep duration affects weight gain [ 47 , 48 ], which is consistent with the findings of this study.…”
Section: Discussionsupporting
confidence: 92%
“…A previous study indicated that longer sleep duration (>9 h) was significantly associated with an increased risk of obesity in adults, while shorter sleep duration had no effect on obesity [ 46 ]. In contrast, other studies showed no evidence that sleep duration affects weight gain [ 47 , 48 ], which is consistent with the findings of this study.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, The frequency of poor sleep was higher in people who were overweight and obese. However, the data show no statistically significant correlation between participants' PSQI scores and BMI [28]. Kong et al [29] concluded that 8.6% (n = 442) of adults reported poor sleep quality in Ningbo.…”
Section: Discussionmentioning
confidence: 93%
“…The prevalence is high among the people with a higher BMI, that is, approximately 10% among those in the second and third stages of obesity. NES displays a positive correla-tion with body weight in several studies (11)(12)(13)(14). There exists sizeable evidence in the literature on the relationship between NES, anxiety, depression, and BMI (15).…”
Section: Introductionmentioning
confidence: 93%